Persistent organic pollutants, diet and blood cholesterol - Margrét Skúladóttir 1981- (2015)
Background: Persistent organic pollutants are a diverse class of organohalogen compounds which include long chain perfluoroalkyl acids (PFAAs) such as perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), as well as legacy contaminants such as the polychlorinated biphenyls (PCBs) and pesticides such as dichlorodiphenyltrichloroethane (DDT) and hexachlorobenzene (HCB). Given the persistent nature of these chemicals and long elimination half-lives examining their sources of exposure and potential adverse consequences on health is of considerable public health importance. Aims: One aim of this thesis was to examine in an observational setting dietary exposures to PFOS and PFOA in addition to examining the association between circulating levels of these two chemicals and blood cholesterol. Secondly we wanted to examine the role of frequent consumption of farmed Atlantic salmon, 3 times a week over 8 weeks, on circulating levels of PCBs, pp'-DDE and HCB. Methods: A cohort of 965 Danish pregnant women was recruited in 1988-89, blood samples were provided and the women reported their diet in week 30 of gestation. From those, 854 women had information on serum cholesterol, serum PFAAs and dietary intake available. Multivariate regression was used to analyse the association of diet with serum concentrations of PFOA and PFOS, and the association PFAAs and total-cholesterol. Furthermore, a total of 40 participants were selected from a previously conducted randomized controlled dietary intervention trial of 8-week duration. 20 were selected from the control group (not consuming seafood) and 20 from the salmon group (consuming 450 g of farmed Atlantic Salmon a week). Serum levels of PCB, pp'-DDE and HCB were measured in baseline and endpoint in all samples. Results: Intake of meat and meat products was positively associated while intake of vegetables was inversely associated (p for trend<0.01) with changes in PFOS and PFOA concentrations. Dietary fat was however associated with serum cholesterol. After ...